Motyw papugi w mozaikowej dekoracji kościoła św. Apostołów w Madabie (578‑579) - Głowa, Anna (Vox Patrum, 2024)
A parrot is one of the most frequently depicted birds in Roman and Late Antique art and it becomes particularly popular in the fifth to sixth centuries in the area of Syro-Palestine. In the Church of the Holy Apostles in Madaba from 578-579, dozens of representations of parrots create a pattern covering the surface of the mosaic floor in the nave, with a medallion depicting the personification of the sea, Thalassa, in the centre. The article attempts to answer the question of the significance of the parrot motif in this particular church and the reason for its popularity in Late Antique art in general. The first part of the article presents parallels for a composition based on the recurring parrot motif found in houses, synagogues and churches in the period under discussion. The second part of the article analyses the written sources relating to this bird, as well as its earlier representations in Greco-Roman art, which allows to understand the network of associations that the parrot evoked. On this basis, it is possible to conclude that the parrot was an integral part of a visual language expressing concepts related to prosperity, the richness of nature and its cyclical rebirth, ’paradisiacal’ gardens, and bliss. The contexts in which the parrot is mentioned in Christian texts suggest that it may have been part of iconographic programmes proclaiming the praise of the created world and the power of the Creator.